APLIKASI MODEL CAMEL DALAM MENGUKUR KESEHATAN DAN KINERJA KEUANGAN BANK - HERISPON HERISPON; RORI KRESNA HADE (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2016)
The theme of the article is the banks and financial institutions. The research objective is: to measure the levels of health and financial performance of the bank. This research uses descriptive quantitative method, which analyzed data collected from the literature and data from the company. The data has been collected, then analyzed the financial ratios related to the health of banks and compared from year to year, but it also provides an assessment of the financial performance according to the standards and regulations of Bank Indonesia. The financial statements of the bank is the overall economic transactions undertaken by the bank concerned during an accounting period are classified and systematically arranged into the shape of the balance sheet and income statement. The financial statements of the bank balance sheet providing information to external parties, such as central banks, public and investors, regarding our financial position, which further can be used externally to assess the magnitude of the risks that exist in a bank. An income statement provides an overview of the business development bank. One way to determine the financial performance of banks is the financial statements. The financial statements present all operational activities of the bank in a given period. Based on those statements, do the analysis of the level of of the bank's financial performance, to see the progress and financial condition of the company and also to see the performance.